Increasing public awareness of probiotics and environmental issues through the promotion of fermented beverage products - Sari, Ni Nyoman Tri Puspa; Mulyadewi, I Gusti Agung Ayu Candra; Wijayani, Putu Ayu Diah; Putra P, Komang Widhya Sedana; Lasmi, Ni Wayan (Nur Science Institute, 2025)
This community service activity aimed to raise public awareness regarding the health benefits of probiotics and the importance of environmental responsibility in managing plastic waste. Awareness of healthy lifestyles, especially in the consumption of functional foods like probiotics, is still relatively low among Indonesian students. Although probiotics are proven to support digestive health, many still perceive fermented drinks such as Yakult as regular beverages without recognizing their health value. Additionally, plastic waste from product packaging remains an environmental issue. This program implemented a practical and educational approach through socialization, field observation, and an industrial visit to PT Yakult Indonesia Persada in Mojokerto on June 24, 2025. The activity involved 120 participants aged 18–30, including students and young educators. They received information about probiotics and health, observed the production process, and learned about sustainable waste management based on the 3R (Reduce, Reuse, Recycle) principles. The results showed increased knowledge and motivation among participants to adopt healthier and more environmentally conscious behavior.